Peningkatan Kesadaran Pengelolaan Sampah di Kawasan Pesisir Ekowisata Bale Mangrove melalui Edukasi dan Inovasi - Hidayat, Sugih Akbar; Ahmadin, Ahmadin; Nazifa, Syuhada; Ananda, Sri Devi; Fitri, Novita Mariana; Syukur, Abdul; Handayani, Baiq Sri; Sukma, Izza Melati (Universitas Mataram, 2025)
Mangrove ecosystems play an important role in maintaining the balance of the coastal environment, but are still faced with challenges of waste pollution and lack of public awareness. The Biology Education Thematic KKN activity at the University of Mataram in Bale Mangrove Ecotourism aims to increase public awareness of waste management and mangrove ecosystem conservation. The methods used include practice-based education, such as training in making organic fertilizer using the Takakura method, ecobrick competitions, installation of waste nets, and the activity “Sunrise Nyampah.” The results showed an increase in community awareness and participation in maintaining environmental cleanliness and the important role of mangroves in coastal ecosystems. In conclusion, this program successfully supports the development of Bale Mangrove Ecotourism as a sustainable educational destination by combining environmental conservation and community empowerment.